Analysis and comparison of community garden indicators using network analysis process (ANP) - Ramin Alivand; Omid Noori; Hadi Veisi; Reza Deihimfard (علوم محیطی, 2023)
Introduction: Beginning and developing community gardens in city by creating a healthy and intimate atmosphere, it has made people feel refreshed and by increasing social, cultural and political participation It can be helpful in solving people's problems in the region, city and even the country. By creating a community garden, in addition to continuing to maintain the gardens, can also benefit from the services and functions of these gardens. In this research using Network analysis and ranking of indicators and their relationships in the decision-making process.Material and methods: This research was conducted in Karaj city, based on different criteria and according to the opinion of framework experts to develop Community gardens Provide multi-function and multi-service. to reach this goal, used from the model provided for the services and functions of the community garden which has eight economic, political, social, cultural, ecological, environmental, educational and health dimensions, And with 125 components. In this research, data collection Using a questionnaire Based on ANP decision technique and pairwise comparisons by professionals with at least 15 years of experience which were selected by the snowball method. After calculating the geometric mean of the judgments made the information entered the software. The processing and analysis of the results of this research was done using Excel and Super decision software.Results and discussion: After measurement the weight of the used indicators, the final prioritization for the proposed functions and services was done by the super decisions software. Among the investigated indicators Stability index (2C) with a weight of 0.389 The most important indicator of choosing the services and functions of the community garden and after this index, Acceptability index (3C) with a weight of 0.228 and effectiveness index (1C) with a weight of 0.205 They were ranked next. Based on the calculation with weighted indicators, Among the functions of community garden dimensions The economic dimension of "Using Abandoned Lands", social dimension of "entertainment space", political dimension of "tourism", cultural dimension of "developing garden endowment culture", environmental dimension of "pollution reduction", ecological dimension of "biodiversity", health dimension "healthy body weight", educational dimension of "Environment for promoting agriculture" They got the highest priority.Conclusion: The results of this research can in showing the position of the community garden very useful by people and officials and to justify investment in order to benefit from the services and functions of the community garden. Due to the importance of the community garden, when designing the city, there should be a plan to provide urban green infrastructure. Based on the knowledge of services and functions of these gardens to be considered necessary in accordance with social preferences.